Location and Workspace Analysis of 2（2-UPR+RPU） Serial-parallel Hybrid Mechanism - Ren Xin; Bo Ruifeng; Wu Xiaowei; Li Ruiqin (Jixie chuandong)
In order to overcome the shortcomings of the parallel mechanism used in express delivery industry， such as small motion space and limited application scope，a 2 （2-UPR+RPU） series-parallel hybrid mechanism is proposed based on the 2-UPR+RPU low-DOF parallel mechanism. The inverse position solution and workspace analysis are carried out in order to be applied in industrial production. Firstly，the hybrid mechanism is modeled in SolidWorks，and its degree of freedom is obtained by analyzing the screw theory. Then，the position inverse solution of the mechanism is solved by continuous method. Finally，the motion simulation is carried out in SolidWorks by using CAD variable geometry method and the track data of the processing points are obtained，and the workspace is obtained by using Matlab software. The workspace of 2 （2-UPR+RPU） hybrid mechanism is much larger than that of single-layer parallel mechanism，and its shape is regular and symmetrical. The 2（2-UPR+RPU） hybrid mechanism has both the flexibility of series mechanism and the high rigidity and precision of parallel mechanism. Through corresponding program control，it can replace manual work.